An assessment of the relationship between public real estate markets and stock markets at the local, regional, and global levels - Kim Hiang Liow; Felix Schindler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
The primary contribution of this study is to assess whether public real estate markets and stock markets are linked at the local, regional, and global levels, and to assess the evolution of their dynamic relationship and gradual integration during the last two decades. For individual pairs of real estate and stock markets, our analysis shows that the current levels of local, regional, and global correlation between real estate and stock markets are time-varying and are, at most, moderate at the respective integration levels. The real estate and stock markets are both contemporaneously and causally linked in their returns and volatilities; however the causality relationship appears weaker. In the long run, the real estate markets have slowly become more integrated with the global and regional stock markets; while less integrated with the local stock markets. In addition, the extracted common factors allow for a direct assessment of the dynamic relationships between the real estate and stock markets as a group, and thereby complement the individual results. Finally, there appears to be a declining real estate and stock return dispersion and differential at the local, regional, and global levels for all nine economies, indicating a tendency of return convergence between real estate and stock market in an international environment.
Keywords: C32; G31; 330; Time-Varying Integration; Return and Volatility Causality; Multivariate Asymmetric DCC-GARCH; Return Convergence; Securitized Real Estate Markets; International Stock Markets